THE INFLUENCE OF LIQUIDITY, CAPITAL INTENTGSITY, AND SALES GROWTH ON TAX AVOIDANCE MODERATED BY FIRM SIZE - Hanifah Nur Azizah; Ahmad Jayanih (ZILLZELL MEDIA PRIMA, 2026)
This study examines the effect of liquidity, capital intensity, and sales growth on tax avoidance, with firm size as a moderating variable, in consumer cyclicals companies listed on the Indonesia Stock Exchange during 2021–2024. The research uses secondary data from annual reports and applies panel data regression with the Fixed Effect Model. The results show that sales growth and firm size significantly affect tax avoidance, while liquidity and capital intensity do not have a significant effect. Furthermore, firm size is not able to moderate the relationship between liquidity and capital intensity on tax avoidance, but it significantly moderates the effect of sales growth on tax avoidance. Collectively, all variables significantly influence tax avoidance. Overall, the findings indicate that company performance and firm scale play a more important role in determining tax avoidance behavior, whereas short-term financial capability and asset structure are not the main determinants.